2004
DOI: 10.1088/0957-4484/15/3/026
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube film based on single-wall carbon nanotubes for strain sensing

Abstract: Carbon nanotubes change their electronic properties when subjected to strains. In this study, the strain sensing characteristic of carbon nanotubes is used to develop a carbon nanotube film sensor that can be used for strain sensing on the macro scale. The carbon nanotube film is isotropic due to randomly oriented bundles of single-wall carbon nanotubes (SWCNTs). Using experimental results it is shown that there is a nearly linear change in voltage across the film when it is subjected to tensile and compressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
299
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(302 citation statements)
references
References 15 publications
3
299
0
Order By: Relevance
“…MWCNT-Pluronic buckypaper specimens were fabricated using vacuum filtration (figure 1) [24,42]. An advantage of using vacuum filtration is that the density of film constituents (i.e., nanotubes and polymers) can be precisely controlled.…”
Section: Nanocomposite Fabricationmentioning
confidence: 99%
“…MWCNT-Pluronic buckypaper specimens were fabricated using vacuum filtration (figure 1) [24,42]. An advantage of using vacuum filtration is that the density of film constituents (i.e., nanotubes and polymers) can be precisely controlled.…”
Section: Nanocomposite Fabricationmentioning
confidence: 99%
“…A study by Dharap et al [4] showed that pure SWCNT films ('bulky paper') can serve as strain sensors if they are bonded to the structural surface as conventional strain sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have excellent mechanical properties and a wide range of applications, such as structural elements for nano-electromechanical systems and nanocomposites [1,2]. Mechanical behaviors of CNTs or CNTs in various surroundings have been widely investigated by experiments, molecular dynamic simulations and continuum mechanics models [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have potential importance in the use as basic elements of nanoscale devices such as chemical and mechanical sensors [2,14]. The reliability of many devices depends critically on the understanding of the responses of CNTs to external loadings, thus studying the dynamic buckling be-havior of MWNTs or MWNTs in an elastic medium is of great importance.…”
Section: Introductionmentioning
confidence: 99%